2020
DOI: 10.26656/fr.2017.4(4).025
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening, phenolic acid profiling and antioxidant activity analysis of peels from selected mango (Mangifera spp.) genotypes in the Philippines

Abstract: Peels of thirteen (13) ripe mango genotypes were analyzed for total phenolic, total flavonoid, vitamin C, vitamin A contents, and antioxidant activity. Statistical analysis showed that the mango genotypes were significantly different in all the chemical assays performed. The total phenolic content of the genotypes ranged from 3.44-14.59% GAE while total flavonoid content ranged from 0.32 – 2.16% CE. The vitamin A and vitamin C contents of mango peels ranged from 24.66 – 92.01 IU/g and 4.55 – 6.40 mg/g, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…To calculate the β-carotene and vitamin A content of the samples, the method described by Ocampo et al [ 26 ] was employed. Extraction was carried out in an ice bath for 5 min with a solvent:sample ratio of 1:10 g respectively, using ethanol as solvent.…”
Section: Methodsmentioning
confidence: 99%
“…To calculate the β-carotene and vitamin A content of the samples, the method described by Ocampo et al [ 26 ] was employed. Extraction was carried out in an ice bath for 5 min with a solvent:sample ratio of 1:10 g respectively, using ethanol as solvent.…”
Section: Methodsmentioning
confidence: 99%
“…A previously described technique was used to estimate the β-carotene and Vitamin A content [29]. First, 1 g of each sample was added to the extraction stage along with 10 mL of ethanol, and the mixture was stirred at room temperature for 30 min at 300 rpm.…”
Section: β-Carotene-vitamin a Contentmentioning
confidence: 99%
“…Though this study suggests anti-oxidants potential, it is suggested that at least three anti-oxidants activity assays should be conducted to determine the anti-oxidants activity of a compound to increase the validity of the experiment (Ocampo et al, 2020). Further investigations are also required to reveal other active constituents present.…”
Section: In Vitro Anti-oxidants Assaymentioning
confidence: 97%
“…Mohan et al (2013) had IC50 of 35.05 μg/mL and 32.45 μg/mL respectively when compared to ascorbic acid, which had an IC50 of 22.11 μg/mL, and Itoh et al (2020) had IC50 of 6.87 and 5.76 μg/mL respectively when compared to ascorbic acid, which had an IC50 of 1.30 μg/mL. A study by Ocampo et al (2020) also revealed that the other parts of Mangifera indica also exhibit significant anti-oxidants activity as well as the leaves, which supports the findings in this study (Ocampo et al, 2020).…”
Section: In Vitro Anti-oxidants Assaymentioning
confidence: 97%
See 1 more Smart Citation